The ECB's Policy, the Recovery Fund and the Importance of Trust: The Case of Greece - Vasiliki Dimakopoulou; George Economides; Apostolis Philippopoulos (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper, using a microfounded macroeconomic model that embeds the key features of the Greek economy, studies the efficacy of the various policy measures taken, at national and EU level, to cushion the economic effects of the pandemic shock. The paper attempts to give quantitative answers to questions like: What are the effects of these policies and, especially, what are the implications of the fiscal transfers and grants from the Recovery Fund and the quantitative policies of the ECB, like the PEPP, for the Greek economy? Do they help the real economy and, if yes, by how much? What would have happened had these measures not taken? How costly will be the re-emergence of the fear of debt default and risk premia?
Keywords: E50; E60; F30; 330; central banking; fiscal policy; international lending; pandemic